Comparison of coagulation performance and floc properties using a novel zirconium coagulant against traditional ferric and alum coagulants - Jarvis, Peter; Sharp, Emma; Pidou, Marc; Molinder, Roger; Parsons, Simon A.; Jefferson, Bruce (Elsevier Science B.V., Amsterdam., 2012)
Coagulation in drinking water treatment has relied upon iron (Fe) and aluminium (Al) salts throughout the last century to provide the bulk removal of contaminants from source waters containing natural organic matter (NOM). However, there is now a need for improved treatment of these waters as their quality deteriorates and water quality standards become more difficult to achieve. Alternative coagulant chemicals offer a simple and inexpensive way of doing this. In this work a novel zirconium (Zr) coagulant was compared against traditional Fe and Al coagulants. The Zr coagulant was able to provide between 46 and 150% lower dissolved organic carbon (DOC) residual in comparison to the best traditional coagulant (Fe). In addition floc properties were significantly improved with larger and stronger flocs forming when the Zr coagulant was used with the median floc sizes being 930 υm for Zr; 710 υm for Fe and 450 υm for Al. In pilot scale experiments, a similar improved NOM and particle removal was observed. The results show that when optimised for combined DOC removal and low residual turbidity, the Zr coagulant out-performed the other coagulants tested at both bench and pilot sca